Two kinds of pink: development and difference in Germanic colour semantics. (May 2015) - Vejdemo, Susanne; Levisen, Carsten; van Scherpenberg, Cornelia; Guðmundsdóttir Beck, þórhalla; Næss, Åshild; Zimmermann, Martina; Stockall, Linnaea; Whelpton, Matthew
Abstract: This article traces the birth of two different pink categories in western Europe and the lexicalization strategies used for these categories in English, German, Bernese, Danish, Swedish, Norwegian and Icelandic with the cognate sets pink, rosa, bleikur, lyserød, ceris. In the 18th century, a particular shade of light red established itself in the cultural life of people in Western Europe, earning its own independent colour term. In the middle of the 20th century, a second pink category began to spread in a subset of the languages. Contemporary experimental data from the Evolution of Semantic Systems colour project (Majid et al., 2011) is analysed in light of the extant historical data on the development of these colour terms. We find that the current pink situation arose through contact-induced lexical and conceptual change. Despite the different lexicalization strategies, the terms' denotation is remarkably similar for the oldest pink category and we investigate the impact of the advent of the younger and more restricted secondary pink category on the colour categorization and colour denotations of the languages. Highlights: Traces the birth of two different pink concepts in Western Europe. Studies lexicalization strategies of pink concepts in seven Germanic languages. Analyses experimental data in light of historical data. Contact-induced lexical and conceptual change shaped the current pink situation.